Abuse of tropicamide eye drops: review of clinical data - Bellman,Val (2022)
Over the past 15 years, the increasing nonmedical use of tropicamide ophthalmic drops has been reported in Europe, coinciding with an increase in opioid addiction and drug-related mortality. Although tropicamide is generally known as a cheap alternative to heroin in Eastern Europe, it still appears to be a relatively new phenomenon that has arisen over the last decade. A narrative review was conducted of all the relevant sources published in more than five countries between January 1, 1975 and January 10, 2021. For bibliographic accuracy, the materials published in Russian and Italian were professionally translated to English. During the preparation of this report, we were able to interview five Russian-speaking patients who injected tropicamide in the past and we discuss another case of intravenous tropicamide use. This review was acknowledged by the institutional review board of the University of Missouri-Kansas City. All patients interviewed at the Unica Medical Center consented for their clinical information to be reported in a medical publication. We analyzed data from 50+ various sources and covered a variety of drug-related issues, including information on the extent, patterns, and trends in tropicamide use, its health consequences, and other clinical findings. The information provided in this article may help providers better detect tropicamide abuse and incorporate new rehabilitation strategies into the management of these patients.